Heterogeneous 2D/3D Tin‐Halides Perovskite Solar Cells with Certified Conversion Efficiency Breaking 14%. Issue 36 (23rd July 2021) - Yu, Bin‐Bin; Chen, Zhenhua; Zhu, Yudong; Wang, Yiyu; Han, Bing; Chen, Guocong; Zhang, Xusheng; Du, Zheng; He, Zhubing
Abstract: As the most promising lead‐free one, tin‐halides based perovskite solar cells still suffer from the severe bulk‐defect due to the easy oxidation of tin from divalent to tetravalent. Here, a general and effective strategy is delivered to modulate the microstructure of 2D/3D heterogeneous tin‐perovskite absorber films by substituting FAI with FPEABr in FASnI3 . The introduction of 2D phase can induce highly oriented growth of 3D FASnI3 and it is revealed in the optimal 2D/3D film that 2D phase embraces 3D grains and locates at the surfaces and grain boundaries. The FPEA + based 2D tin‐perovskite capping layer can offer a reducing atmosphere for vulnerable 3D FASnI3 grains. The unique microstructure effectively suppresses the well‐known oxidation from Sn 2+ to Sn 4+, as well as decreasing defect density, which leads to a remarkable enhanced device performance from 9.38% to 14.81% in conversion efficiency. The certified conversion efficiency of 14.03% announces a new record and moves a remarkable step from the last one (12.4%). Besides of this breakthrough, this work definitely paves a new way to fabricate high‐quality tin‐perovskite absorber film by constructing effective 2D/3D microstructures. Abstract : A general and effective strategy is delivered to modulate the 2D/3D microstructure of tin‐perovskite films by introduction of a 2D phase with the function of FPEABr, which induces high‐orientation growth of 3D FASnI3 by embracing the 3D grains at their surfaces and boundaries. That leads to a breakthrough of device performance of 14.81% in power conversion efficiency, along with 14.03% certified.